2021
DOI: 10.1101/2021.11.15.21266268
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Gut-bladder axis syndrome associated with recurrent UTIs in humans

Abstract: Recurrent urinary tract infections (rUTIs) are a major health burden worldwide, with history of infection being a significant risk factor. While the gut is a known reservoir for uropathogenic bacteria, the role of the microbiota in rUTI remains unclear. We conducted a year-long study of women with and without history of rUTIs, from whom we collected urine, blood and monthly fecal samples for multi-omic interrogation. The rUTI gut microbiome was significantly depleted in microbial richness and butyrate-producin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 64 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Whether UPEC gut presence alters the immune system’s response to eventual bladder exposure remains an open question. Our recent work revealed a significant depletion of butyrate producers in women with rUTI history regardless of immediate UTI status as well as tentative evidence for differential immune markers at healthy time points compared with a healthy cohort ( 11 ). While considerable work is needed to further explore these dynamics, we propose that the gut-bladder axis may be an as yet overlooked, but relevant, driver of rUTI susceptibility.…”
Section: The Gut As An Agitatormentioning
confidence: 63%
See 1 more Smart Citation
“…Whether UPEC gut presence alters the immune system’s response to eventual bladder exposure remains an open question. Our recent work revealed a significant depletion of butyrate producers in women with rUTI history regardless of immediate UTI status as well as tentative evidence for differential immune markers at healthy time points compared with a healthy cohort ( 11 ). While considerable work is needed to further explore these dynamics, we propose that the gut-bladder axis may be an as yet overlooked, but relevant, driver of rUTI susceptibility.…”
Section: The Gut As An Agitatormentioning
confidence: 63%
“…While current evidence remains limited due to the lack of appropriate cohort studies, recent work has shown that children with UTIs ( 9 ) and kidney transplant patients with bacteriuria ( 10 ) have differential microbiome structures compared with respective control cohorts, suggesting a link between the resident microbiota and uropathogen gut colonization and/or transmission to the bladder. Furthermore, our recent longitudinal cohort study identified reduced microbial diversity and lower levels of butyrate-producing bacteria in the guts of women with rUTI history compared with healthy controls ( 11 ). Antibiotic treatment of UTIs is certainly a confounder in such studies due to the resulting perturbations of the gut microbiota associated with repeated exposure.…”
Section: The Gut As a Bystandermentioning
confidence: 95%
“…It should be noted, that all the examined patients had increased levels of sIg A and myeloperoxidase activity in coprofiltrates, which suggested enteric inflammation, while only 20% had clinical symptoms of gut dysbiosis. These data have been recently confirmed in a year-long study by Worby et al in which the authors showed strong similarities between gut dysbiosis in RUTIs and inflammatory bowel disease characterized by depleted levels of butyrate-producing bacteria and diminished microbial richness (Worby et al, 2021). Moreover, the authors found a higher plasma marker of intestinal inflammation, eotaxin-1, in women with RUTIs compared to healthy controls, suggesting low-level enteric inflammation (Worby et al, 2021).…”
Section: Is Intestinal Barrier Dysfunction Clinically Significant In ...mentioning
confidence: 66%
“…These data have been recently confirmed in a year-long study by Worby et al in which the authors showed strong similarities between gut dysbiosis in RUTIs and inflammatory bowel disease characterized by depleted levels of butyrate-producing bacteria and diminished microbial richness ( Worby et al, 2021 ). Moreover, the authors found a higher plasma marker of intestinal inflammation, eotaxin-1, in women with RUTIs compared to healthy controls, suggesting low-level enteric inflammation ( Worby et al, 2021 ). The presence of such subclinical enteric inflammation in patients with RUTIs indicates the formation of a vicious circle.…”
Section: Introductionmentioning
confidence: 64%
“…Although the intestinal and bladder dynamics of Escherichia coli were similar between cohorts, the rUTI strain that colonized the intestine was not cleared for a long time by antibiotic treatment. They concluded that a distinct immune response to bacterial invasion of the bladder is potentially mediated by the gut microbiome [ 76 ]. This is evidence for the gut–bladder axis.…”
Section: Substances Involved In Crosstalkmentioning
confidence: 99%